2005
DOI: 10.1007/s10495-005-6065-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria induce expression of apoptosis in human spermatozoa

Abstract: An increased number of sperm undergoing apoptosis has been observed during inflammatory processes in the male genital tract, which might be associated with elevated reactive oxygen species (ROS) levels. However, another factor to stimulate apoptosis could be the direct contact with bacteria or its products, even in the absence of ROS. The aim of this study was to investigate whether bacteria can directly initiate apoptosis in human spermatozoa. Human spermatozoa selected by density gradient centrifugation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 25 publications
3
77
0
4
Order By: Relevance
“…For example E. coli strains are known for their ability to immobilize and damage the morphology of spermatozoa by direct contact, mediated by attachment organelles such as pili or type-1 fimbriae (projections) and mannose receptor-dependent interactions (68). Also, the sperm surface is rich in glycoproteins and is therefore susceptible to the nitration of bacteria such as E. coli, C. trachomatis, U. urealyticum, Staphylococcus haemolyticus and Bacteroides ureolyticus with spermatozoa leading to the loss of sperm motility and normal morphology (1).…”
Section: The Effects Of Bacterial Infection On Sperm Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…For example E. coli strains are known for their ability to immobilize and damage the morphology of spermatozoa by direct contact, mediated by attachment organelles such as pili or type-1 fimbriae (projections) and mannose receptor-dependent interactions (68). Also, the sperm surface is rich in glycoproteins and is therefore susceptible to the nitration of bacteria such as E. coli, C. trachomatis, U. urealyticum, Staphylococcus haemolyticus and Bacteroides ureolyticus with spermatozoa leading to the loss of sperm motility and normal morphology (1).…”
Section: The Effects Of Bacterial Infection On Sperm Parametersmentioning
confidence: 99%
“…and C. albicans. They can induce the expression of apoptosis in the male genital tract during inflammatory processes (68).…”
Section: The Effects Of Bacterial Infection On Sperm Chromatin Condenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in the absence of ROS, a direct role of bacteria inducing apoptosis in human sperm has been demonstrated [Villegas et al 2005]. Using an in vitro model, reported that bacteria trigger oxygen radical release and LPO.…”
Section: Introductionmentioning
confidence: 99%
“…Page 10 of 24 A c c e p t e d M a n u s c r i p t 10 stress and apoptosis of spermatozoa was also observed following incubation with E. coli (Villegas et al, 2005;Fraczek et al, 2007). In rat in vivo models the retrograde inoculation of E. coli into the vas deferens promoted clinically recognizable acute orchitis characterized by severe degeneration of germinal epithelial cells, tubular atrophy, moderate inflammation and mild interstitial fibrosis with subsequent testicular damage (Demir et al, 2007).…”
Section: Impairment Of Testicular and Sperm Function By E Colimentioning
confidence: 99%